A Improved Sexual Satisfaction Following Hyaluronic Acid Penile Filler Injection: A Case Report - I Kadek, Aribowo; Pramesemara, I Gusti Ngurah (Universitas Airlangga, 2025)
Background : Sexual satisfaction is a fundamental human need, and penis size is often regarded as an important factor for sexual satisfaction among men. Research indicates that penis size can also play a significant role in sexual satisfaction for women. Case : This case report details the experience of a 37-year-old man who felt that his genital size was inadequate, leading to dissatisfaction during sexual intercourse.The patient underwent penile filler treatment using Hyaluronic Acid (HA), receiving a total of 12 cc. Following the injection, there was an increase in the circumference of his penis by 2 cm, resulting in improved patient satisfaction. Before the HA filler injection, the patient had an Index of Male Genital Image (IMGI) score of 58. A follow-up evaluation conducted one month later revealed an increase in the IMGI score to 70. Discussion : Non-surgical penis enlargement procedures are commonly performed because they have a lower risk compared to surgical options. The most popular method involves the injection of hyaluronic acid (HA) fillers. This procedure is effective in enhancing sexual satisfaction, as it leads to a noticeable increase in the circumference of the penis, resulting in more fulfilling sexual experiences. HA fillers are biocompatible, long-lasting, and have a low incidence of complications or serious side effects. Conclusion : This case demonstrates that Hyaluronic Acid is effective in enhancing the diameter of the penis and improving patient satisfaction.